Awareness of Breast cancer and current perspectives: An overview - Pooja G Singh; Kanthesh M Basalingappa; Gopenath Ts; Navya Raj Mp; Prathibha Rajashekara S; Sushma Bv (International Journal of Pharma and Bio Sciences, 2021)
Breast cancer is the most common diagnosed cancer form experienced in women and is second among women for the susceptibility of cancer fatality. Typically it is illness noticed among the individual of reproductive age in women. In the previous and current research data has shown a positive impact on improving the clinical outcome of breast cancer. It has become apparent in recent years that breast cancer is not a sign of single disease rather than a variety of molecular tumours from breast epithelial cells. This was due to the advances made in the control, inspection, diagnosis, and therapeutic strategies of breast cancer. Individualized therapeutic life style care often could improve the effectiveness of treatment and thereby lower rates of mortality. However, there is a significant inhibition effect and existing challenges noticed with respect to disease control, insufficient forecasts for Triple negative breast cancer (TNBC), and drug resistance. Cell lines tend to be a crucial element for molecular diagnostics in breast cancer, as they can be used extensively as in vitro models in cancer research in many areas of laboratory research and in particular. Breast cancer cells represent a very significant candidate, because they are used in various groups of ER-positive tumours with varying levels of nuclear receptor expression in research into estrogen receptor (ER)-positive breast cancer cell testing and several sub- clones which are identified. Likewise, the growing prevalence and mortality of breast cancer among the population in the developing world is a central concern. This review finding specially emphasises on current diagnostic screening technique, treatment strategies and potential limitations for breast cancer prognosis.